Kajian Literatur Pada Identifikasi Risiko Pada Pemeliharaan Gedung - Naluri, Nike; Purba, Humiras Hardi (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
Naturally there is no object made by humans that cannot be demagerd. and over time, there are many changes both physically and financially in the finished building but its useful life can be extended by carrying out regular repairs through an activity known as maintenance. . The purpose of this study was to determine the type of risk, location and year of research related to risks in building maintenance. The method used in this study is a literature review. 45 Journals obtained online from various sources with the keywords risk on building maintenance. From these journals, it can be concluded that the highest type of risk in building maintenance is internal technical risk and project technicality, where most research locations are carried out in Indonesia and the most research year is in 2020.